Potential danger of the negative impact of professional women's sports on the reproductive function of sportswomen - O.I. Tsyhanenko; Y.V. Pershehuba; L.V. Bohdanovych; N.A. Skliarova (Publishing House TRILIST, 2022)
The article is a review of modern achievements in the field of studying reproductive health problems among professional sportswomen. Long-term and intensive physical loads are used for professional female athletes in the training process in speed-strength sports at levels that were historically characteristic only for male athletes. Insufficient awareness of this problem among doctors, trainers, and athletes can be considered as an actual problem of the potential danger for the reproductive function of female athletes during professional sports. Specialists in the field of the impact of high physical exertion on the reproductive health of female athletes have to face a complex of problems. The medical problems include female athlete triad, relative lack of energy, disruption of endocrine regulation due to the use of doping and contraceptives, and hyperandrogenism. Pedagogical problems include contradiction between the desire to achieve high sports results and the conscious, even indifferent attitude of the coaching staff to the physiological characteristics of women and the lack of relevant knowledge on the part of female athletes and their parents. The well-known female athlete triad - amenorrhea, anorexia and the lack of energy syndrome - has a neuroendocrinology basis caused by genetic, physiological factors and high physical loads. These data should be brought to the attention of coaches, female athletes and their parents. It was proposed algorithm for the prevention of reproductive health of professional athletes. Conclusions. High performance sports pose an additional risk for women's reproductive health. Doping, contraception and neglecting the peculiarities of the menstrual cycle are a threat to the future life and health of female athletes. The risk group consists of young athletes. An important approach to solving the problem is to inform of various specialties doctors, first of all obstetricians-gynecologists, endocrinologists, sports doctors, nutritionists, as well as trainers and athletes themselves, about the potential danger of the possible negative impact of professional women's sports on their reproductive function and about the measures that are necessary to be carried out to prevent the development of this danger.